2015
DOI: 10.1016/j.jenvman.2015.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Inherent organic compounds in biochar–Their content, composition and potential toxic effects

Abstract: Pyrolysis liquids consist of thermal degradation products of biomass in various stages of its decomposition. Therefore, if biochar gets affected by re-condensed pyrolysis liquids it is likely to contain a huge variety of organic compounds. In this study the chemical composition of such compounds associated with two contaminated, high-volatile organic compound (VOC) biochars were investigated and compared with those for a low-VOC biochar. The water-soluble organic compounds with the highest concentrations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 324 publications
(863 reference statements)
2
119
0
Order By: Relevance
“…The different kinds of organic compound except the 2,4-DCP appeared in the solution, which could have been attributed to the enhanced effects of BCs (Ghidotti et al 2017). Several low molecular weight organic compounds produced during the pyrolysis could also have been responsible for 2,4-DCP sorption by BCs (Buss et al 2015). …”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…The different kinds of organic compound except the 2,4-DCP appeared in the solution, which could have been attributed to the enhanced effects of BCs (Ghidotti et al 2017). Several low molecular weight organic compounds produced during the pyrolysis could also have been responsible for 2,4-DCP sorption by BCs (Buss et al 2015). …”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Several research groups [68,69] have studied the effect of PAH under water leaching conditions in soil, or have further quantified polar as well as non-polar tar components because especially polar compounds such as phenols are believed to have phytotoxic effect on some plants growth; those compounds are not included in the EPA 16 PAH method. There are no conclusive studies so far on the identification and quantification of compounds with a toxic effect and on what plants, therefore it is expected that a number of studies will emerge looking on this issue.…”
Section: Polycyclic Aromatic Hydrocarbon Levelsmentioning
confidence: 99%
“…In [68][69][70] despite the concentrations of the 16 PAHs exceeding biochar guideline values, it was concluded that, the biggest concern for application to soil would be the co-occurrence of volatile organic compounds (VOCs) such as low molecular weight (LMW) organic acids and phenols, as these can be highly mobile and have a high potential to cause phytotoxic effects. Therefore, it is strongly suggested for VOCs to be included among criteria for assessment of biochar quality [68]. In order to avoid significant VOC levels in/on char altogether, sufficient residence time, temperature and/or oxidation is required but in case those criteria are met the condensation of VOC-rich gases onto the char surface must be avoided in the same way as for the PAH-condensation described above.…”
Section: Polycyclic Aromatic Hydrocarbon Levelsmentioning
confidence: 99%
“…Plant responses, however, vary greatly across species and ecosystems, and null or 59 negative biochar effects are common (Jeffery et al, 2011;Spokas et al, 2012). Thus, null and 60 negative responses of plants to biochar have received recent research attention ( Buss & Mašek, 61 2014; Kołtowski & Oleszczuk, 2015;Domene et al, 2015;Buss et al, 2015). 70 of tree seedlings, indicating possible P limitation in boreal soils.…”
mentioning
confidence: 99%
“…Many of the compounds generated are "mobile" (Buss & Mašek, 2014; Buss 86 et al, 2015): they are either water soluble or volatile, i.e., have high vapor pressures under 87 ambient conditions temperatures and pressure conditions (Yu et al, 2007). Such compounds 88 include low molecular weight alcohols, ketones, aliphatic acids, and phenols (Buss et al, 2015; 89 Lievens et al, 2015), as well as larger polyaromatic hydrocarbons (PAHs) (Hale et al, 2012; 90 Kołtowski & Oleszczuk, 2015;Domene et al, 2015). Other mobile and potentially toxic 91 compounds produced during pyrolysis such as salts and heavy metals are generally detected at 92 only low levels in biochars derived from non-contaminated feedstocks (Domene et al, 2015), are 93 strongly sorbed by biochar (Thomas et al, 2013;Lucchini et al, 2014), and are therefore less 94 likely to be an important component of toxicity responses to biochars (Buss & Mašek, 2014; 95 Kołtowski & Oleszczuk, 2015;Domene et al, 2015;Lievens et al, 2015).…”
mentioning
confidence: 99%